Agricultural Extension in An Urban Informal Settlement During COVID-19: The Effectiveness of the “Tanimang Bayan” Initiative in Sitio San Roque, North Triangle, Quezon City - Patrice Bianca R. Yapjoco (CSID Journal of Infrastructure Development)
The COVID-19 pandemic exposed deep inequalities in food access, particularly in urban informal settlements. This study examines the effectiveness of the “Tanimang Bayan” initiative, an urban agriculture project implemented in Sitio San Roque, Quezon City, as a form of agricultural extension during the pandemic. The research adopts a qualitative approach, drawing on data from key informant interviews, participant observation, and secondary sources. Findings indicate that the initiative provided a localized response to food insecurity by enhancing access to fresh produce and promoting community-led production. It also supported collective action and self-organization among residents, strengthening their autonomy in navigating structural limitations. These outcomes suggest that community-based agricultural interventions can contribute meaningfully to resilience-building and local food systems in marginalized urban contexts.